2003
DOI: 10.1002/aic.690490709
|View full text |Cite
|
Sign up to set email alerts
|

Flocculation of biological cells: Experiment vs. theory

Abstract: Flocculation of biological cells is important in the biotechnology industry, as it could

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 50 publications
1
44
0
Order By: Relevance
“…Population balance models have been used to describe the growth of microbial cells (8)(9)(10)(11)(12) and other processes (13)(14)(15). They are based on the fact that the properties of the cell culture such as the age distribution of the cells present are not uniform but evolve with time.…”
Section: Introductionsupporting
confidence: 38%
“…Population balance models have been used to describe the growth of microbial cells (8)(9)(10)(11)(12) and other processes (13)(14)(15). They are based on the fact that the properties of the cell culture such as the age distribution of the cells present are not uniform but evolve with time.…”
Section: Introductionsupporting
confidence: 38%
“…For the flocculated feed streams, although the modal particle size increases, the actual particle size distribution is broadened, as shown in Figure 3. In an earlier study, Han et al (2003) showed that flocculation of CHO cells often leads to a self-similar steady-state floc size distribution. Thus, some small particulate matter and cell debris remain.…”
Section: Discussionmentioning
confidence: 49%
“…Beyond typical industrial processes, agglomeration plays a role in diverse bio-related applications such as blood flow dynamics and bio-molecular cross-linking of particles (Han et al 2003, Hiddessen et al 2004.…”
Section: Introductionmentioning
confidence: 45%